Application of P6 Acupressure on Children with Acute Lymphoblastic Leukemia Experiencing Post-Chemotherapy Nausea and Vomiting - Arindya, Sekar Ayu Putri; Utami, Tuti Asrianti (JURNAL CITRA KEPERAWATAN, 2025)
Cancer refers to a condition where cells grow uncontrollably, potentially harming nearby healthy tissues and spreading via the lymphatic system and bloodstream. Among various types of leukemia, Acute Lymphoblastic Leukemia (ALL) is the most frequently found in pediatric patients. Chemotherapy, the primary treatment, often causes nausea and vomiting, affecting the child's comfort and nutritional intake. This study aimed to evaluate the effectiveness of P6 acupressure therapy in reducing nausea and vomiting in children with ALL. A case study was conducted involving two children undergoing chemotherapy at unit Anggrek, RS X, Jakarta. P6 acupressure was applied for 3–4 consecutive days. Results indicated a significant decrease in nausea intensity and vomiting frequency in one patient, while the other showed a mild reduction. The findings demonstrate that P6 acupressure is an effective, non-pharmacological nursing intervention for managing chemotherapy-induced nausea and vomiting in pediatric patients. This therapy can be safely taught to caregivers as part of home-based supportive care, providing practical implications for nursing practice in pediatric oncology settings.